IMPACT OF SERVICES AND PRICES ON CONSUMER DECISIONS IN MM 46 WAY EAST LAMP - Sugiono Sugiono; Susi Sulastri; Hikmatul Aliyah, Aliyah; Ichsan Ichsan (Utan Kayu Publishing, 2024)
This research is quantitative research using survey methods. The sample technique used is purposive sampling. The total sample in this study is 100 MM46 Way Jepara consumer respondents who have made a purchase transaction. Data processing techniques use validity tests, realism tests, classical assumption tests and hypothesis tests. The software used to analyze the data is SPSS 16.0. The results of this study using the T-Test showed that (1) Quality of Service has a partial influence on a purchase decision with a significance of 0.003. (2) Price has an influence partial on a buying decision with the significance value of 0.038. (3) Quality of the Service, and Price has a simultaneous influence upon a decision of purchase with a significant value of 0.000.